The Study of Signs in Frida (2002): Exploring the Creative Nexus between the Film and the Paintings (Social Science Review, 2025)
The symbiotic link between the film Frida (2002) and the artworks of the Mexican painter Frida Kahlo were examined with this study. In order to locate the Frida Kahlo paintings that were included in the film, this study analyses how they relate to the plot and settings, in a qualitative methodology. The formal analysis of those paintings discovered that they were used in a variety of ways to enhance the story in the film, including: to provide Kahlo's thoughts a visual expression, to offer comments on the film's topics and to establish a feeling of continuity between the many scenes. The semiotic analysis on denotative and connotative meaning was applied on the relevant scenes of the film Frida (2002). According to the study's findings, combining film and art can be a potent approach to communicate a story and produce a visually appealing film experience.Social Science Review, Vol. 41(1), June 2024, Page 91-120.